2017
DOI: 10.1111/poms.12739
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Cellular Bucket Brigades with Hand‐Off Times

Abstract: A cellular bucket brigade is a way to coordinate workers along an aisle with work content on both sides. Each worker in a cellular bucket brigade works on one side of the aisle when he proceeds in one direction, and he works on the other side when he proceeds in the reverse direction. Although the cellular bucket brigade eliminates the unproductive walk‐back, it requires more hand‐offs to assemble a product than a traditional (serial) bucket brigade. These hand‐offs may waste significant production capacity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Previous research has not examined the role of individual differences and alternative production factors in a nonserial production line environment. Previous production line research has focused on situations where workers have no choice but to extend help to other workers such as in the bucket brigade (e.g., Bartholdi & Eisenstein, ; Lim, ), where faster workers must help slower workers on completing a production task (Doerr et al, , , ; Schultz et al, ). Thus, workers are motivated to assist other workers because of mandated instructions to provide help.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has not examined the role of individual differences and alternative production factors in a nonserial production line environment. Previous production line research has focused on situations where workers have no choice but to extend help to other workers such as in the bucket brigade (e.g., Bartholdi & Eisenstein, ; Lim, ), where faster workers must help slower workers on completing a production task (Doerr et al, , , ; Schultz et al, ). Thus, workers are motivated to assist other workers because of mandated instructions to provide help.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has focused on situations where workers do not have a choice but to extend help to other workers. In the bucket brigade (e.g., Bartholdi & Eisenstein, 1996;Lim, 2017), workers are organized in a serial fashion from slowest to fastest, and faster workers are instructed that they must help slower workers to complete the production task (Doerr et al, 1996;Doerr, Freed, Mitchell, Schriesheim, & Zhou, 2004;Doerr, Mitchell, Schriesheim, Freed, & Zhou, 2002;Schultz et al, 1998). Thus, workers are motivated to assist other workers because of the mandated instruction to provide help.…”
Section: Introductionmentioning
confidence: 99%
“…Lim and Wu [14] describe a protocol to coordinate pickers on a U-line for maximum productivity. Lim [15] considers the effects of hand-off times on the operational performance of cellular bucket brigades. Bucket brigade order picking, however, consistently experiences productive losses because of picker blocking [16] and hand-off delays [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…After analysis, different types have different balance points. Lim (2017) found that although the CBB model reduces the nonproductive behavior of employees, the handover is time-consuming and labor-intensive. However, his research shows that even if there is a handover, the capacity of CBB is about 50% higher than that of the traditional BB line.…”
Section: Introductionmentioning
confidence: 99%